Integrability of the continuum Bessel wavelet kernel - Upadhyay S.K.; Singh R. (My University, 2025)
In this paper, the sufficient condition for the integrability of the kernel of the inverse Bessel wavelet transform is obtained by using the theory of Hankel transform and Hankel convolution. © 2015 World Scientific Publishing Company.